Age-related alterations in the activation of trunk and lower limb muscles during walking - Marques, Nise Ribeiro [UNESP]; Hallal, Camilla Zamfolini; Spinoso, Deborah Hebling [UNESP]; Crozara, Luciano Fernandez [UNESP]; Morcelli, Mary Hellen [UNESP]; Karuka, Aline Harumi [UNESP]; Navega, Marcelo Tavella [UNESP]; Goncalves, Mauro [UNESP] (Ios Press, 2016)
BACKGROUND: Walking is a complex motor task that requires an integrated coordination of the trunk, lower limb, and upper limb movements. Previously, few studies have investigated the activation pattern of trunk muscles during walking. However, the mechanisms by how aging affects the recruitment of trunk muscles during walking remain unclear. OBJECTIVE: The present study aimed to compare the activation of trunk and lower limb muscles during walking in younger and older women. METHODS: Fifteen younger women between 18 and 30 yr and 19 older women between 60-82 yr walked on the treadmill at a self-selected speed, while 1-min surface electromyography (EMG) signals were recorded from the multifidus, internal oblique, gluteus maximus, rectus femoris, biceps femoris, tibialis anterior, and gastrocnemius lateralis. EMG signals were processed and a linear envelope was calculated at an initial stance (50 ms after heel contact) and final stance (50 ms before toe-off). RESULTS: Compared with younger women, older women had 52.32% lower activation of the internal oblique (p = 0.027) and 39.95% lower activation of the rectus femoris (p = 0.003) at initial stance. CONCLUSION: Results of this study demonstrated that older women had lower activation of trunk and knee muscles during the initial stance, which may have resulted from weakness and balance impairments caused by aging.
Keywords: Aging; gait; electromyography; trunk stability